1990
DOI: 10.1073/pnas.87.23.9383
|View full text |Cite
|
Sign up to set email alerts
|

A series of prostaglandin F2-like compounds are produced in vivo in humans by a non-cyclooxygenase, free radical-catalyzed mechanism.

Abstract: A series of prostaglandin F2-like compounds are produced in vivo in humans by a non-cyclooxygenase, free radical-catalyzed mechanism ( ABSTRACTIncreasing attention has focused on the role of free radicals derived from oxygen in the pathophysiology of a wide variety of disorders. One of the well-recognized targets of free radical-induced iWury is peroxidation of lipids. Using a variety of approaches, we have found that a series of prostaglandin F2-like compounds are produced in vivo in humans by a non-cyclooxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
1,201
3
16

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,754 publications
(1,238 citation statements)
references
References 14 publications
18
1,201
3
16
Order By: Relevance
“…Regarding the potential significance of 8-iso-PGF 2α signaling, it is important to note that isoprostanes can be produced in vivo at levels that are several orders of magnitude higher than classical prostaglandins/thromboxanes [2]. Consequently, the biological effects of these signaling pathways could substantially impact cellular function in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the potential significance of 8-iso-PGF 2α signaling, it is important to note that isoprostanes can be produced in vivo at levels that are several orders of magnitude higher than classical prostaglandins/thromboxanes [2]. Consequently, the biological effects of these signaling pathways could substantially impact cellular function in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…While the prostaglandins are produced as a result of cyclooxygenase enzyme activity, isoprostanes are generally thought to form nonenzymatically by free radical-mediated peroxidation of arachidonic acid (AA) [2]. Separate evidence has suggested that cyclooxygenase activity may also contribute to isoprostane production in selected tissues [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The isoprostanes were originally discovered in 1990 by Morrow et al, [64] and are now believed to act as potent mediators of oxidative injury [64][65][66][67][68]. As such, the isoprostanes are mainly generated from arachidonic acid non-enzymatically and are synthesised in situ in phospholipids and then released through the actions of phospholipases, such as phospholipase A 2 [64,65]. A wide range of prostanoid-like isoprostanes is generated including the PGF 2α -, the PGD 2 -, and PGE 2 -series [64,69].…”
Section: Isoprostanes and Tp Receptor Activationmentioning
confidence: 99%
“…As such, the isoprostanes are mainly generated from arachidonic acid non-enzymatically and are synthesised in situ in phospholipids and then released through the actions of phospholipases, such as phospholipase A 2 [64,65]. A wide range of prostanoid-like isoprostanes is generated including the PGF 2α -, the PGD 2 -, and PGE 2 -series [64,69]. The F 2 series are the most common and one of these compounds 8-epi PGF 2α , also recently termed iPF 2α -III [69], is the most abundant isoprostane generated in situations of oxidative injury [64][65][66][67][68][69].…”
Section: Isoprostanes and Tp Receptor Activationmentioning
confidence: 99%
“…8‐Epi‐prostaglandin F 2α (8‐epi‐PGF 2α ) is formed from peroxidation of arachidonic acid19 and is detectable in human plasma and urine. The quantification of 8‐epi‐PGF 2α has been widely used as a noninvasive method to assess lipid peroxidation 20, 21.…”
Section: Introductionmentioning
confidence: 99%